The Role of Donor‐Specific HLA Alloantibodies in Liver Transplantation. Issue 4 (1st March 2014) - O'Leary, J. G.; Demetris, A. J.; Friedman, L. S.; Gebel, H. M.; Halloran, P. F.; Kirk, A. D.; Knechtle, S. J.; McDiarmid, S. V.; Shaked, A.; Terasaki, P. I.; Tinckam, K. J.; Tomlanovich, S. J.; et al.
<x xml:space="preserve">Abstract</x> The impact of donor‐specific HLA alloantibodies (DSA) on short‐ and long‐term liver transplant outcome is not clearly defined. While it is clear that not all levels of allosensitization produce overt clinical injury, and that liver allografts possess some degree of alloantibody resistance, alloantibody‐mediated adverse consequences are increasingly being recognized. To better define the current state of this topic, we assembled experts to provide insights, explore controversies and develop recommendations for future research on the consequences of DSA in liver transplantation. This article summarizes the proceedings of this inaugural meeting. Several insights emerged. Acute antibody‐mediated rejection (AMR), although rarely diagnosed, is increasingly understood to overlap with T cell–mediated rejection. Isolated liver allograft recipients are at increased risk of early allograft immunologic injury when preformed DSA are high titer and persist posttransplantation. Persons who undergo simultaneous liver–kidney transplantation are at risk of renal AMR when Class II DSA persist posttransplantation. Other under‐appreciated DSA associations include ductopenia and fibrosis, plasma cell hepatitis, biliary strictures and accelerated fibrosis associated with recurrent liver disease. Standardized DSA testing and diagnostic criteria for both acute and chronic AMR are needed to distil existing associations into etiological processes in order to develop responsive therapeutic strategies.